Diction in Poetry Anthology Surat Kopi by Joko Pinurbo as A Poetry Writing Teaching Material - Anindita, Kun Andyan; Satoto, Soediro; Sumarlam, Sumarlam (International Journal of Active Learning, 2017)
This research shows the diction of Joko Pinurbo in ten letter-themed poetries in poetry anthology of Surat Kopi using a stylistic approach. The poetries included Surat Cukur, Surat Kopi, Surat Kau, Surat Batu, Surat Pulang, Surat Libur, Surat Sarung, Surat Malam, Surat Senyap, Surat Kabar. The stylistic approach was chosen because stylistics is one of the linguistic disciplines that studies the uniqueness or the isiosyncrasy of the use of language in literary works, especially poetry that can bring certain effects. This study used descriptive qualitative method. This type of qualitative descriptive research was used to describe the aspects to be described. The results of this study indicated that in ten poetries with the theme of the letter there were 4 types of diction used: denotative, connotative, concrete and abstract diction. The denotative and concrete dictions were widely used dictions in the ten poetries. The effect was it was not confusing for the reader because it is very minimal use of figurative language. The poetries were explicit and did not generate many interpretations but still promising the depth of meaning. Thus, the ten poetries of Joko Pinurbo in this anthology could be used as a material for teaching Indonesian literature for students. The simplicity of the poetries could ease the students to learn and to try writing their own poetries with uncomplicated dictions, such as denotative diction and concrete diction that did not employ many figurative languages.